Entidades não lucrativas de Uberlândia: um estudo psicanalítico sobre a lógica discursiva solidária diante das novas formas de subjetivação - Melazo, Ana Paula Soares Ferreira (2010)
The theme of this dissertation involves the non-profit entities, represented mostly by NGOs, using them as a focal point for discussion of solidarity inherent to their speeches. Returning to the political, historical and social giving rise to such civil society initiative, we ve found many factors that led us to realize a social process of politicization since the 1980s. Nowadays, we can observe the interference of globalization and neoliberalism in the weakening of the state as a promoter of social welfare s policies. In this context, the logic of the market went into effect more strongly in the world, so that, the social sectors are contracted by the State, which led to the subsequent mobilization of civil society s layers initiatives that include private stamp, however, with public funds for the implementation of their actions. These, in turn, will be offered to the population as services that can be consumed, minimizing the possibilities of political participation. Using psychoanalysis to seek understandings applicable to this social setting, were raised theoretical assumptions related to a typical logic discursive of solidarity movements. Following this logic, would present the mechanisms used in the contemporary world to escape the helplessness associated with narcissism, masochism and traumatic. Eleven interviews were conducted in three nonprofits in the city of Uberlândia, in order to understand how to structure the logical discursive management of helplessness in these institutions. The analysis of the interviews led us to the understanding of a common logic to the discourse of the institutions. The main mechanisms found in the discourse of solidarity were four. One was the narcissistic splitting as a resource removal of the conflictive construction through a harmonious speech, which provides a second mechanism: the idealization. This is present in a context in which the subject itself is able to see how powerful and capable of promoting a harmonious world. As a result, the omnipotence is made as collateral to cover the subject that the fault is on the other, and not himself. The subject of joint action in this context is how you get that knowledge and power. However, on this mastery condition, this solidarity action s person seem like a slave in the face of the necessity of keeping himself on this omnipotent in front of the helplessness s condition. The fourth mechanism was found to deliver this masochistic among the subjects of joint action. Considering the results, the reflections directed to the needs of establishing horizontal links to cope with the helplessness, the recognition of otherness and political expression.